Risk Factors for Osteoporosis in Postmenopausal Women: A Cross-Sectional Analysis - Al-Tameemi, Ahmed Ghanawi Alwan (American Journal of Biomedicine and Pharmacy, 2025)
Background: Osteoporosis represents a significant public health concern, particularly among postmenopausal women. While established risk factors exist, the relative contribution and interaction of these factors in different populations remain incompletely understood. Objective: This study aimed to identify and quantify the prevalence and relative impact of modifiable and non-modifiable risk factors for osteoporosis in a diverse cohort of postmenopausal women. Methods: A cross-sectional study was conducted among 742 postmenopausal women aged 50-80 years. Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (DXA). Data on demographic characteristics, lifestyle factors, medical history, and biochemical parameters were collected. Multiple logistic regression analyses were performed to identify independent risk factors associated with osteoporosis. Results: The prevalence of osteoporosis in the study population was 32.6%. Significant independent risk factors included age (OR=1.08 per year, 95% CI: 1.05-1.11), low body mass index (OR=2.64 for BMI <22 kg/m², 95% CI: 1.87-3.72), early menopause (OR=1.92, 95% CI: 1.34-2.76), family history of osteoporosis (OR=2.17, 95% CI: 1.53-3.08), smoking (OR=1.76, 95% CI: 1.21-2.56), low calcium intake (OR=1.89, 95% CI: 1.38-2.59), and physical inactivity (OR=2.09, 95% CI: 1.51-2.89). Vitamin D deficiency, alcohol consumption, and prolonged corticosteroid use were also significantly associated with increased osteoporosis risk. Conclusion: Numerous modifiable and non-modifiable risk factors for osteoporosis in postmenopausal women were discovered in this study; the highest correlations were seen for early menopause, low BMI, physical inactivity, and family history. According to our research, risk assessment instruments that take these variables into account might improve the early detection of high-risk patients and enable focused preventative measures.